Analysis of Hemodiialysa (HD) Services Based on Comparison of Hospital Tariff Calculations With BPJS Health Rates - Wahyuni, Ni Nyoman Tri; Suartawan, I Wayan; Wardana, Putu Adi Arya (Jurnal Manajemen Bisnis, Akuntansi dan Keuangan, 2024)
To thrive and advance, hospitals must effectively manage fierce competition within the healthcare sector. Remaining competitive necessitates hospitals to reevaluate their existing pricing tactics, particularly by adopting a competitive pricing framework. After engaging in conversations with the head of the hemodialysis (HD) department, it came to light that the BPJS program accounted for 95% of the HD patients at Wangaya Hospital, while the remaining 5% comprised general patients. This study used a descriptive, quantitative research method. The investigation focused on the Hemodialysis service unit and its related departments, including service, finance, technician, IPSRS, IPSRS waste management, and pharmacy departments.